Aeromechanics of self-twisting blades in high-speed slowed rotor flight - Ward, E.; Chopra, I.; Datta, A. (My University, 2017)
This paper describes the effects of a composite coupled blade spar on the performance of a slowed RPM helicopter rotor in high speed edgewise flight. This study shows that antisymmetric composite coupling in the spar of a UH-60A-like rotor can provide a significant increase in the efficiency when the RPM is reduced. A comprehensive analysis was performed using a full 3D FEA based aeroelastic computational structural dynamics (CSD) solver, X3D, with the inclusion of a freewake aerodynamics model. This was first validated using existing UH-60A full-scale wind tunnel test data for high advance ratios. The current study shows that a composite blade can achieve a maximum increase in the lift to drag ratio of approximately 1.3 (20% improvement) at 85% of the nominal RPM (NR) of 27 rad/s. This efficiency gain is achieved through a combination of delayed stall drag along the retreating side of the rotor and reduced negative lift along the advancing side. A further RPM reduction to 65NR showed a maximum efficiency improvement of 15% and was attributed only to the alleviation of negative lift on the advancing side. A hygrothermally stable Winckler layup was shown to perform just as well as a nominal coupled layup at 85NR, and marginally better at 65NR, in addition to contributing to practical manufacturability of the rotor design. Close study of the strains in the rotor showed that a rotor with an extension-torsion coupled composite spar would be within the realm of practical manufacturability as the axial strains around the azimuth fell well within IM7/8552’s allowable tensile strain of 6000 ????????. Tensile strain is directly related to the amount of twist change in the rotor and is reduced when the RPM is slowed and the rotor untwists towards its original cold shape.